Pengaruh Kepuasan Kerja, Komitmen Karyawan dan Disiplin Kerja Terhadap Kinerja Karyawan Conato Bakery Denpasar Barat - Ariningsih, Ni Putu Alit; Susanti, Putu Herny; Purwaningrat, Putu Atim (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Conato Bakery presents the Lifestyle Bakery concept, engaged in selling bread with the mission of Go Green and Stay Healthy. The purpose of this study was to determine the partial and simultaneous effect of job satisfaction, employee commitment and work discipline on employee performance at Conato Bakery West Denpasar. The population in this study were all employees at Conato Bakery West Denpasar, consisting of 30 employees. Determination of the sample using a saturated sample technique, namely the entire population is used as a sample. After the instrument test and classical assumption test were carried out, then the data was analyzed using multiple linear regression analysis, determination, t test, and F test. The results of the partial analysis show that job satisfaction and work discipline have a positive and significant effect on employee performance. Employee commitment has a negative and insignificant effect on employee performance. Job satisfaction, employee commitment and work discipline simultaneously have a positive and significant effect on employee performance